IL-6/IL-12 superfamily of cytokines and regulatory lymphocytes play critical roles in the etiology and suppression of CNS autoimmune diseases - Yadav, Manoj Kumar; Singh, Samara P.; Egwuagu, Charles E. (Frontiers in Immunology, 2025)
Cytokines influence cell-fate decisions of naïve lymphocytes and determine outcome of immune responses by transducing signals that regulate the initiation, intensity and duration of immune responses. However, aberrant regulation of physiological levels of cytokines contribute to the development of autoimmune and other inflammatory diseases. The Interleukin 6 (IL-6)/IL-12 superfamily of cytokines have a profound influence on all aspects of host immunity and our focus in this review is on the signaling pathways that mediate their functions, with emphasis on how this enigmatic family of cytokines promote or suppress inflammation depending on the physiological context. We also describe regulatory lymphocyte populations that suppress neuroinflammatory diseases by producing cytokines, such as IL-27 (i27-Breg) or IL-35 (i35-Breg and iTR35). We conclude with emerging immunotherapies like STAT-specific Nanobodies, Exosomes and Breg therapy that ameliorate CNS autoimmune diseases in preclinical studies.